CALCULATIONS OF TIDAL CURRENTS IN BAY LAGOON (NHA TRANG BAY) USING FINITE ELEMENT METHOD - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2014)
At present, development activities are vigorously going on in Bay lagoon (Nha Trang bay). Therefore, investigation into the natural and environmental conditions in this area, including the study and calculations of current regime is very necessary and pressing. However, modeling the current regime in this lagoon is not simple task because of many islands located in the study area … Their existence makes the long wave transmission into the bay more complex and local-specific. Therefore, as we study the current regime here, great attention is paid to the detailization of the coastal boundaries. Using the finite element method (FEM) for calculating the tidal currents has solved difficulties which have been faced by the finite difference method (FDM) used previously. Initial research results show that the outcomes by FEM agreed well with the field data measured at random times. From the results computed by FEM, we have following remarks on the tidal current regime in this bay: At ebb tide, tidal current velocity can reach 22.9 cm/s with direction of 137.30, usually at 19.2 m in depth. At flood tide, tidal current velocity can reach 19.4 cm/s with direction of 353.80, at 1.0 m in depth. The comparison between the modeling sea levels and field measurements at the same position shows the largest deviation being 19.1 cm, the average being 10 cm, and the smallest one being 0.